Medicine use in institutions of long permanence for aged of Fortaleza-CearÃ: profile, risks and necessities - Wiviany Thaise de Lima Mendes (2006)
Many of the elderly that lives in Nursing Homes (ILPI) have health problems, are very fragile and frequently need polypharmacy, being exposed to health risks like medical lapsing errors, dispensation or drug administration. Thus, the rational drug use in these ILPI is essentially linked to its drugs dispensary and to one adjusted Pharmaceutical Assistance. To investigate the conditions of the drugs dispensary and the Pharmaceutical Assistance, moreover, to evaluate the quality of the prescribed drugs to the elderly in ILPI in Fortaleza. A descriptive study was carried out in two ILPI (A and B) at Fortaleza-CE. On the first study, were observed and evaluated the conditions of functioning of the drug dispensary, the profile of the existing products in the dispensary, the employees and the routines related to the processes of election, acquisition, storage, control and distribution of drugs in those institutions. The data collected were inserted and analyzed on a data base developed on the Microsoft Excel 2002 program. On the second study, an analysis of the quality of medicines prescribed to the aged residents in the ILPI was carried out, considering the essentiality, the drug association in fixed doses, the pharmacological interaction potential, the drug-food interaction potential, the redundancy of pharmacotherapy and the therapeutic value of the drug. The data collected were inserted and analyzed in the statistical program SPSS 12.0 for Windows. The project was submitted to the Committee of Ethics in Research at the Hospital Complex of the Federal University of the CearÃ, receiving approval. First Study: In the dispensary of the ILPI-A there was an infestation of insects in the drugs; lack of illumination control, ventilation and temperature of the environment; and, storage of not-recommended products (cigarette, match sticks and others). Moreover, among the 776 pharmaceutical specialties found in the dispensary, 67.9% needed medical lapsing, 75.5% were monodrugs and 21.2% were essential. And, of the total of 195.177 pharmaceutical units, almost 30% were in improper conditions for consumption. The storage of the products was not standardized. The election and standardization of drugs were not realized and the acquisition of drugs was realized without logistic evaluation of supply. The collective system of drug distribution was used. The dispensary was managed by employees without training. In the ILPI-B, there was a lack of illumination control, ventilation and temperature in the environment; windows without protecting screens against the entrance of rodents and insects; and a lack of routine for cleaning the place. 104 pharmaceutical specialties were found, 51.9% needed medical lapsing, 87.5% were monodrugs and 58.7% were essential. In the 21.447 pharmaceutical units, only 1.7% was improper for consumption. The storage of the products obeyed alphabetical order for generic name, being registered the entrance and exit in proper card indices. The election and standardization of drugs were realized, and, were annually acquired. The collective system of drug distribution was used. The dispensary was managed by trained employees. Second Study: In ILPI-A, 50.8% were female, 51.6% were functional dependents individuals and 53.2% were between 60 and 75 years old. Of the 347 pharmaceuticals specialties prescribed, 5.5% were associatiated to drugs in fixed dose, 30.5% was not essential and, 34.9% was for the central nervous systems (CNS). It was observed that 25.6% of drugs presented unacceptable therapeutic value for the elderly. Among the medical lapsings with 2 or more drugs, 52.6% presented potential drug interactions. In ILPI-B, 58.3% were female, 100% were functional dependents individuals and 65% were between 60 and 75 years old. Of the 205 pharmaceuticals specialties prescribed, 2.9% were associatated to drugs in fixed dose, 32.2% was not essential and, 55.1% were to the CNS. It was observed that 36.6% presented unacceptable therapeutic value for the elderly. Among the medical lapsings with 2 or more drugs, 58.0% presented potential drug interactions. In both ILPI, the potential risks to health of the elderly, due to the drug use, were related to the lack of technician-administrative orientation concerning the drug, the dispensary management and the Pharmaceutical Assistance. The profile of the dispensaries and prescribed medicines suggests that the elderly of these ILPI are in constant risk of health, maximized or increased by incorrect and irrational use of drugs. The development of a structuralized Pharmaceutical Assistance, starting with the observance the effective good practices of the legislation in the country about the processes related to the Cycle of the Pharmaceutical Assistance, the implantation and implementation of steps of prevention as the reduction of the polypharmacy, reduction of the unacceptable drug use by the elderly, the evaluation of the quality of prescribed medicines and the practice of the Pharmaceutical Attention and the Clinical Pharmacy are fundamental.